Evaluation of Antibacterial Properties of Metal Brackets Coated with Graphene Oxide Nanoparticles and Its Synergistic Effect with Other Metal Oxides – An In-Vitro Study (Orthodontic Journal of Nepal, 2023)
Introduction: The intricate design of the orthodontic brackets creates a favorable environment for plaque formation, resulting in an increased risk of decalcifiation and white spot lesions. Many preventative and adjunctive procedures are required to mitigate the negative effects of orthodontic therapy. With the progress of nanotechnology, orthodontics has benefited immensely. The main objective of the study is to evaluate the antibacterial property of metal brackets coated with various concentrations of Graphene Oxide nanoparticles and its synergistic activity with other metal oxides.Materials and Method: In this study, 120 metal pre-adjusted premolar brackets are equally divided in to 6 Groups based on various concentrations of graphene oxide nanoparticles and their synergistic activity with other metal oxides. The antibacterial properties are evaluated for each group.Result: Brackets coated with GO 1wt% have shown statistically signifiant antibacterial property among the subgroups. The synergistic antibacterial action of GO+AgTiO2 have shown statistically signifiant antibacterial action compared to other metal oxides. The Antibacterial property of the groups are as follows: GO+AgTiO2 > GO 1wt% > GO+ZnO > GO 0.5wt% > 0.25wt% > Control.Conclusion: The metal orthodontic brackets coated with Graphene oxide and its synergistic activity with other metal oxides have shown statistically signifiant antibacterial properties with no cytotoxicity affects to Human gingival firoblasts.